Developing web-based learning media for enhancing digital literacy in computer networking - Buchori, Achmad; Rahmadhani, Tarisa Ahwalia; Rozzaqi, Ade Ricky; Khoiri, Nur (Indonesian Journal of Educational Development (IJED), 2025)
This study aimed to develop web-based learning media for computer networking to improve students’ digital literacy. The research employed a Research and Development (R&D) approach, utilizing the ADDIE model, and was conducted at SMA Negeri 1 Pecangaan with 35 students and one teacher as participants. Instruments included expert validation sheets, questionnaires, and pre-test and post-test assessments. The media obtained a high feasibility score from experts (content = 87.50%; media design = 85.42%). Student responses also indicated a high level of practicality (83.61%). Statistical analysis confirmed significant learning improvement: the experimental group (M = 82.74, SD = 4.21) outperformed the control group (M = 74.11, SD = 4.85), with a t-test result of t(68) = 5.47, p < .001. N-Gain analysis revealed that the experimental group achieved a score of 0.75 (high category), compared to 0.64 (medium category) in the control group. These results demonstrate that the developed web-based media is both feasible and effective for enhancing digital literacy in computer networking.